2015
DOI: 10.1136/eb-2014-101982
|View full text |Cite
|
Sign up to set email alerts
|

Family-focused treatment improves attenuated psychotic symptoms, but does not differ from brief treatment in negative symptoms and social functioning in ultra high risk patients aged 12–35 years

Abstract: FROM: Miklowitz DJ, O'Brien MP, Schlosser DA, et al. Family-focused treatment for adolescents and young adults at high risk for psychosis: results of a randomized trial. J Am Acad Child Adolesc Psychiatry 2014;53:848-58.WHAT IS ALREADY KNOWN ON THIS TOPIC? Transition to psychotic episode can be reduced to about 50% by psychosocial interventions such as cognitive behavioural therapy (CBT), but there are no improvements in negative symptoms and social functioning. 1 2 Antipsychotic medications are not usually in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first study showing with longitudinal data that better family functioning is a protective factor for PT. This finding supports the idea that improving family functioning may have a positive impact in terms of symptomatic evolution ( 50 ), and that early family intervention, in dysfunctional families, could prevent PT in UHR subjects ( 24 , 25 , 51 53 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study showing with longitudinal data that better family functioning is a protective factor for PT. This finding supports the idea that improving family functioning may have a positive impact in terms of symptomatic evolution ( 50 ), and that early family intervention, in dysfunctional families, could prevent PT in UHR subjects ( 24 , 25 , 51 53 ).…”
Section: Discussionsupporting
confidence: 83%
“…Another study showed that the behavior of the family toward the UHR subject modified the outcome, with “positive remarks” and “signs of affection” (parental warmth), respectively, leading to a reduction in negative symptoms and improved social functioning ( 24 ). Conversely, one study found that family therapy improved positive symptoms, but not negative symptoms or social functioning ( 25 ). Criticisms from family members are linked to high levels of cortisol, a marker of stress, in patients and especially in UHR patients ( 26 ).…”
Section: Introductionmentioning
confidence: 99%